Managerial and client - related problems associated with immunization in the Adansi East District of Ashanti - Ghana - Osei, Francis (2011)
A thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirements for the award of Master of Science degree in Health Services Planning and Management, 2001